Effectiveness Of Lime Juice Administration (Citrus Aurantifolia) On Nausea Vomiting In Pregnant Women At Matahari Primary Clinic Tj. Morawa - Desideria Yosepha Ginting; Cyntia Deana (JURNAL KEBIDANAN KESTRA (JKK), 2025)
Background: Experiencing nausea or sickness while pregnant is common, especially in the first trimester, and it can have serious consequences for the mother's and foetus' health. Hormonal changes, gastrointestinal sensitivities, and psychological issues are usually associated with these symptoms, which about 70-80% of pregnant women experience. A natural cure that may alleviate nausea is lime, which is abundant in antioxidants and vitamin C. Lime has antiemetic qualities thought to be possessed by ingredients including citric acid and essential oils. When it comes to nausea and vomiting during pregnancy, using lime juice as a supplementary treatment is thought to provide a safer and more instinctual alternative. Objectives: This research is conducted to see if lime juice (Citrus aurantifolia) will help pregnant women who are experiencing nausea and vomiting during the first trimester who visit the Matahari Tj. Morawa Health Clinic. Research Method: This statistical study uses the non-parametric Wilcoxon test with a one-group pretest-posttest design. All moms at the Matahari Tj. Morawa Wellness Clinic who were in their first trimester were part of the research population. The intensity of vomiting was assessed using the PUQE-24, and a collection size of 14 participant was established using Slovin's algorithm. Research Results: At the Matahari Tj. Morawa Health Clinic, pregnant women in their first trimester reported less nausea and vomiting after drinking lime juice (p 0.001). Conclusion: Researchers at the Matahari Tj. Morawa Health Clinic found that pregnant women experiencing nausea and vomiting during the first trimester of their pregnancies found relief by drinking lime juice. The clinic should inform expectant moms about the benefits of lime juice for reducing morning sickness and vomiting, particularly in the first trimester.